22.8k views
4 votes
Simply 7(x-2) -4x +9

User Gpeche
by
4.5k points

2 Answers

6 votes
a(b+c)=ab+bc
7(x-2)=7x-7*2=7x-14
7(x-2)-4x+9=7x-14-4x+9
=3x-5
User Alfred Woo
by
5.5k points
1 vote

For this case we must simplify the following expression:


7(x-2) -4x+ 9

We apply distributive property to the terms within parentheses:


7x-14-4x+ 9

We add similar terms taking into account that:

Equal signs are added and the same sign is placed.

Different signs are subtracted and the major sign is placed.


7x-4x-14+9


3x-5

Answer:


3x-5

User CaseyWebb
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.